Causality relations and causality direction of shallots price changes in east java province, Indonesia - Nuzuliyah, Laila; Hanani, Nuhfil; Toiba, Hery; Sujarwo, Sujarwo (Asian Economic and Financial Review, 2024)
This study examines the existence of market integration and causality between prices at the consumer level and other locations in the shallot market. The time-series price data observed every month from 2013 to 2018 regarding the price level of consumers originating from farmers in Probolinggo, Nganjuk, and Malang districts were analyzed. Additionally, consumer price data was collected in Probolinggo Regency, Nganjuk Regency, Malang Regency, and Surabaya City. The data was analyzed using the Granger causality test. The results revealed significant findings at the producer level, indicating a negative causality between Nganjuk and Probolinggo producer prices. On the other hand, producer markets in Nganjuk, Probolinggo, and Malang districts influence consumer prices in Surabaya City. Finally, Nganjuk Regency, Probolinggo Regency, and Malang Regency’s consumer markets had a negative influence on the Surabaya City consumer market. Market participants, such as farmers and traders, need to be aware of these price dynamics to effectively coordinate their activities and respond to market changes.